Mitochondrial genome complexity in Stemona sessilifolia: nanopore sequencing reveals chloroplast gene transfer and DNA rearrangements - Xie, Yuning; Liu, Wenqiong; Guo, Liwen; Zhang, Xuemei (Frontiers in Genetics, 2024)
Mitochondria are semi-autonomous organelles in eukaryotic cells with their own genome. Plant mitogenomes differ from animal mitogenomes in size, structure, and repetitive DNA sequences. Despite larger sizes, plant mitogenomes do not have significantly more genes. They exhibit diverse structures due to variations in size, repetitive DNA, recombination frequencies, low gene densities, and reduced nucleotide substitution rates. In this study, we analyzed the mitochondrial genome of Stemona sessilifolia using Nanopore and Illumina sequencing. De-novo assembly and annotation were conducted using Unicycler, Geseq, tRNAscan-SE and BLASTN, followed by codon usage, repeat sequence, RNA-editing, synteny, and phylogenetic analyses. S. sessilifolia's mitogenome consisted of one linear contig and six circular contigs totaling 724,751 bp. It had 39 protein-coding genes, 27 tRNA genes, and 3 rRNA genes. Transfer of chloroplast sequences accounted for 13.14% of the mitogenome. Various analyses provided insights into genetic characteristics, evolutionary dynamics, and phylogenetic placement. Further investigations can explore transferred genes' functions and RNA-editing's role in mitochondrial gene expression in S. sessilifolia. his colleagues discovered that the mitochondrial genome of Lactuca sativa exhibited linear, branched, and circular configurations (Kozik et al., 2019).Plant mitogenomes are larger and more complex in nature in comparison to animal mitogenomes, which typically span around 15-17 kb in length. Plant mitogenomes vary in size, ranging from 200 kb to 11 Mb in length, but do not harbor much more genes (Zardoya, 2020). The structure of mitochondrial genomes (mitogenomes) in flowering plants displays remarkable diversity, including variations in size, repetitive DNA sequences, recombination frequencies of extensive repeats, low gene densities, and reduced rates of nucleotide substitution (Rose, 2021;Maliga, 2022). The expansion of plant mitogenomes primarily stems from the accumulation of repetitive sequences and the incorporation of DNA derived from chloroplast and nuclear genomes (